Major Effect of Hydrogen Peroxide on Bacterioplankton Metabolism in the Northeast Atlantic - Federico Baltar (Centre for Ecology and Evolution in Microbial Model Systems (EEMiS), Linnaeus University); Thomas Reinthaler (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Gerhard J. Herndl (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Jarone Pinhassi (Centre for Ecology and Evolution in Microbial Model Systems (EEMiS), Linnaeus University) (PLoS ONE, 2013)
The abstract is available here: https://uscholar.univie.ac.at/o:503221 The abstract is available here: https://uscholar.univie.ac.at/o:503221